Pengaruh Ekstrak Kunyit (Curcuma Domestica Vahl) Terhadap Bobot Badan Ayam Broiler (Gallus Sp) - Pratikno, Herry (BULETIN ANATOMI DAN FISIOLOGI dh SELLULA, 2010)
The research aims was to know the effect of turmerin extract on broiler body weight. Material used in those research was Â 24 male broiler chicks CP 707 strain, and were acclimated during 1 week. Those chickens then allotted into 4 groups of treatment, with 6 replications in each group. Group of treatments were T0: without gave turmerin extract, T1: were given 200 mg/kgbw/day turmerin extract, T2: were given 400 mg/kgbw/day turmerin extract, T3: were given 600 mg/kgbw/day turmerin extract. Turmerin extract was given on capsul shape. Main parameters observed was chicken body weight during 3 weeks dan 6 weeks after treatment. Supporting parameter was chickenâ€™s food consumption. The chicken feed with commercial food (BR1 and BR2), food and drinking were given by ad libitum. The data was analyzed by varians analysis with Split Plot Design and Durcan Multiple Range Test. The result showed that there was no interaction effect between turmerin extract dose and observation time. Turmerin extract dose had significant effect (P<0,05) on mean of body weight , and time of observation had very significant effect(P<0,01) on mean of body weght.